The experience of organizational commitment in community college faculty - Flores, Monica Louise, author; Harbour, Clifford P., advisor (Colorado State University. Libraries, 2008)
Organizational commitment impacts organizations in several ways and is important for organizations to understand how this is experienced by employees. Having committed employees creates a positive organizational climate that is conducive to effective working relationships (Meyer & Allen, 1997). The purpose of this qualitative study is to understand the phenomenon of how community college faculty experience organizational commitment. Committed faculty members can translate the college's goals into the creation of positive learning environments which, in turn, can affect student outcomes and the campus climate. Phenomenology is a methodology that identifies the "essence" of the human experience and gives the researcher an opportunity to explore with participants their multiple experiences (Creswell, 2003). Nine recently tenured faculty were interviewed to understand their lived experiences as community college faculty about organizational commitment. The interviews were open-ended and in-depth to discover the unique, layered experiences that allowed the participants to discuss relevant and perhaps unanticipated topics related to their commitment. As phenomenological data analysis was applied, five thematic structures were identified: (a) Service Attitude; (b) Types of Commitment; (c) Collegial Responsibilities; (d) Collegial Relationships; and (e) Institutional Support. These thematic structures merged into three Dimensions of Organizational Commitment that described and explained participants' experiences: (a) Individual Expectations; (b) Positive Experiences; and (c) Negative Experiences. The meaning of participants' experiences is described and explained through the essence of Courtship.
Keywords: community college; community college faculty; faculty development; organizational commitment; socialization; community college education; colleges and universities; school faculty